2015
DOI: 10.1016/j.neuropharm.2015.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal stress, regardless of concurrent escitalopram treatment, alters behavior and amygdala gene expression of adolescent female rats

Abstract: Depression during pregnancy has been linked to in utero stress and is associated with long-lasting symptoms in offspring, including anxiety, helplessness, attentional deficits, and social withdrawal. Depression is diagnosed in 10-20% of expectant mothers, but the impact of antidepressant treatment on offspring development is not well documented, particularly for females. Here, we used a prenatal stress model of maternal depression to test the hypothesis that in utero antidepressant treatment could mitigate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 62 publications
3
28
0
Order By: Relevance
“…In addition, we detected alterations in transcripts encoding synaptic proteins involved in glutamatergic and GABAergic neurotransmitter systems. Our findings are consistent with other studies examining effects of prenatal insults on amygdalar gene expression which have observed changes in ion transporter complexes, GABAA receptor subunits, as well as ionotropic and metabotropic glutamate receptors (Barrett et al, 2017;Ehrlich et al, 2015;Laloux et al, 2012). Our data, however, identify a number of novel PS responsive transcripts, including genes encoding regulatory proteins known to modulate AMPA receptor trafficking and channel kinetics, such as GSG1L, CACNG5, and CNIH3 (Bissen et al, 2019;Gu et al, 2016), genes encoding proteins involved in postsynaptic stabilization of metabotropic glutamate receptors, such as HOMER3, and GABAA receptor trafficking partner HAP1 (Figure 9) (Mandal et al, 2011;Twelvetrees et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…In addition, we detected alterations in transcripts encoding synaptic proteins involved in glutamatergic and GABAergic neurotransmitter systems. Our findings are consistent with other studies examining effects of prenatal insults on amygdalar gene expression which have observed changes in ion transporter complexes, GABAA receptor subunits, as well as ionotropic and metabotropic glutamate receptors (Barrett et al, 2017;Ehrlich et al, 2015;Laloux et al, 2012). Our data, however, identify a number of novel PS responsive transcripts, including genes encoding regulatory proteins known to modulate AMPA receptor trafficking and channel kinetics, such as GSG1L, CACNG5, and CNIH3 (Bissen et al, 2019;Gu et al, 2016), genes encoding proteins involved in postsynaptic stabilization of metabotropic glutamate receptors, such as HOMER3, and GABAA receptor trafficking partner HAP1 (Figure 9) (Mandal et al, 2011;Twelvetrees et al, 2019).…”
Section: Discussionsupporting
confidence: 93%
“…This study replicates research showing that stress experienced by a pregnant female influences fetal growth and neurobehavioral development [2,3]. Even moderate disturbance for just 25% of pregnancy impaired motor performance, reduced attention span, and increased emotionality.…”
Section: Discussionsupporting
confidence: 88%
“…When severe and sustained, prenatal stress increases the risk for premature birth and low birth weight, and has also been correlated with a predisposition for later health concerns, including obesity, poor glucoregulation and cardiovascular disease [1]. In addition, maternal stress in animals can affect neurobehavioral and motor development and increase stress reactivity [2,3]. However, a close review of this literature indicates the type of disturbance, including severity, and timing, influences the extent of the impact, issues addressed further in the following study.…”
Section: Introductionmentioning
confidence: 99%
“…The serotonin system consists of 15 different receptors that are key players at crucial neurodevelopmental stages, regulating neurogenesis, apoptosis, axon branching and dendritogenesis 11 . Many of the studies included in the synthesis of evidence in the current review, which have been selected on the presence of behavioral outcomes, also include outcomes reflecting brain health from the global to the molecular level: the corticosterone response to stress 74, 81, 96, 100, 123, 124, 126, 130, 135 , brain structure and connectivity 71, 77, 84, 93, 101, 110, 122 , neuronal health 59, 82, 85, 89, 104, 109, 111, 126, 135 , monoamine concentrations in the brain 43, 44, 46, 59, 105, 116, 117, 133, 135, 140, 141 , protein expression in the brain – mainly related to the serotonergic system and neurogenesis 62, 71, 78, 88, 91, 97, 127, 129, 141 , gene expression 76, 94, 96, 112, 113, 120, 121, 123, 137, 141, 143 , and epigenetic modifications 76, 112, 114, 124 .…”
Section: Discussionmentioning
confidence: 99%